Systematic Literature Review: Pengaruh Strategi Pemasaran Digital terhadap Perilaku Konsumen dan Kinerja Bisnis - Sefi Rahmawati; Syifa Fauziya; Nur Aisyah; Muhammad Alkirom Wildan (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This article systematically examines the impact of digital marketing strategies in consumer behavior and business performance using the Systematic Literature Review (SLR) method based on PRISMA strandars. The study analyzed 27 articles from SINTA and Scopus databases published between 2016 and 2025. The findings show that digital marketing not only expands market reach and relevant interactions with cunsumers, thus strengthening customer loyalty. On the other hand, challenger such as changes in platform algorithms, digital fatigue, and data privacy issue have emerged, demanding quik responses from companies and policy makers. This reseach makes an important contribution to the development of digital marketing theory and offers practical guidance for digital marketing theory and offers practical guidance for businesses to design adaptive and effective strategies, while proposing more contextualized and theoretical directions for future research.